Morpho-molecular characterization of napier (Pennisetum purpureum) fodder mutants through SSR markers: Morpho-molecular characterization of Napier (SAARC Journal of Agriculture, 2022)
Napier (Pennisetum purpureum) fodder is an important fodder supporting livestock systems in Bangladesh. Using gamma irradiation we developed 48 Napier fodder mutants which were analyzed through morpho-molecular characterization. Among 48 Napier fodder mutants, 41 mutants were originated by applying radiation (20Gy, 30Gy, 40Gy and 50 Gy) on them. The Napier mutants showed variations in survival rate and fresh weight. The survival rate (0-75%) was observed, 20Gy treated plants produced higher fresh weight in Napier-2, Napier-3, Rokona, Markiron grasses; whereas, 30Gy treated plants produced higher fresh weight in Napier-1, Napier-4 and Pakchong. The total of the alleles found in molecular characterization were 17 and the mean number of allele per locus was 3.4. The PIC value ranged from 0.3047 to 0.6587 having an average of 0.4704 per locus. The highest gene diversity (0.7101) was observed in primer Xipes0093 and the lowest gene diversity (0.3750) was observed in primer PSMP2255, having an average diversity of 0.5286. Pair wise genetic distance values ranged (0.0-1.0) with highest between Napier-2 40 Gy vs (Napier-1control, Napier-2 20Gy Napier-2 30Gy), Napier -3 control, vs (Napier-1control, Napier-2 20Gy Napier-2 30Gy), Napier- 3 20Gy vs (Napier-1control, Napier-2 20Gy Napier-2 30Gy) ,(Napier-3 20Gy, Napier-3 30Gy Napier-1 20Gy, Napier-3 50Gy) vs (Napier -2 20Gy, Napier-3 control, Napier-3 20Gy) etc. The UPGMA displayed five major clusters including sub-clusters. Cluster 5 included the highest number of genotypes (21) and cluster 3 included the lowest number of genotypes (2). The results may be useful for future breeding program for Napier fodder development.SAARC J. Agric., 20(2): 105-119 (2022)